2020
DOI: 10.1007/s00167-020-06020-6
|View full text |Cite
|
Sign up to set email alerts
|

The ankle ligament reconstruction-return to sport after injury (ALR-RSI) is a valid and reproducible scale to quantify psychological readiness before returning to sport after ankle ligament reconstruction

Abstract: Purpose Chronic ankle instability is the main complication of ankle sprains and requires surgery if non-operative treatment fails. The goal of this study was to validate a tool to quantify psychological readiness to return to sport after ankle ligament reconstruction. Methods The form was designed like the anterior cruciate ligament-return to sport after injury scale and “Knee” was replaced by the term “ankle”. The ankle ligament reconstruction-return to sport after injury (ALR-RSI) scale was filled by patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 32 publications
(50 reference statements)
3
37
0
Order By: Relevance
“…In particular, Webster et al [ 33 ] designed a scale of 12 items in patients following anterior cruciate ligament reconstruction (ACLR) to assess their psychological readiness to resume sports. This was followed by the development of numerous psychological assessment scales for return to sport after sport-related injuries, including shoulder instability (SIRSI) [ 8 ], hip arthroscopy with femoroacetabular impingement (FAI) syndrome (Hip-RSI) [ 35 ] or ankle ligament reconstruction (ALR-RSI) [ 28 ]. To date, no tool exists to analyze the psychological readiness after MBG procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Webster et al [ 33 ] designed a scale of 12 items in patients following anterior cruciate ligament reconstruction (ACLR) to assess their psychological readiness to resume sports. This was followed by the development of numerous psychological assessment scales for return to sport after sport-related injuries, including shoulder instability (SIRSI) [ 8 ], hip arthroscopy with femoroacetabular impingement (FAI) syndrome (Hip-RSI) [ 35 ] or ankle ligament reconstruction (ALR-RSI) [ 28 ]. To date, no tool exists to analyze the psychological readiness after MBG procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Despite successful surgery and physical therapy, treatment fails in certain patients or their performance is poorer for no objective physical reason [ 18 ]. Indeed, patients must not only be physically ready but also psychologically prepared to return to sport after surgery [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gerometta et al [ 24 ] reported that a patient’s psychological readiness should be taken into account in the decision to return to sport [ 2 ]. The SIRSI score, like the ACL-RSI [ 11 ], and the ALR-RSI for ankle instability [ 35 ], makes it possible to identify patients who will have psychological difficulty returning to their preinjury sport. Indeed, a significant difference was found in patients’ psychological readiness, quantified by the SIRSI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations